Identification of prognostic biomarkers associated with stromal cell infiltration in muscle‐invasive bladder cancer by bioinformatics analyses. (12th August 2020) - Li, Pan; Cao, Jinlong; Li, Jianpeng; Yao, Zhiqiang; Han, Dali; Ying, Lijun; Wang, Zhiping; Tian, Junqiang
Abstract: Muscle‐invasive bladder cancer (MIBC) is one of the common malignant tumors. Patients with MIBC still have high tumor recurrence and progression rates after surgery. Bioinformatics analysis of stromal infiltration‐related genes in the tumor microenvironment (TME) of MIBC patients was performed in this study to determine the major stromal cells types and biomarkers for their progression and poor prognosis. The ESTIMATE algorithm was applied to evaluate the stromal score and immune score of samples from MIBC patients in The Cancer Genome Atlas (TCGA) and found that stromal score was closely related to the clinical characteristics of the patients. The Gene Set Enrichment Analysis (GSEA) further revealed that stromal cells were involved in biological processes such as activation of leukocytes and positive regulation of cell migration during MIBC progression, as well as PI3K‐Akt, MAPK, and Rap1 signaling pathways. Five hub genes related to prognosis, including ACTA2, COL5A1, DCN, LUM, and PRRX1 were identified by the Weighted Gene Co‐Expression Network Analysis (WGCNA), Protein‐Protein Interaction (PPI), survival analysis, and Oncomine, Gene Expression Omnibus (GEO) database validation. Besides, we identified five stromal cell types associated with overall survival time, among which chondrocytes and fibroblasts were identified as the major stromal cell types through correlation analysis. Finally, the Receiver Operating Characteristic (ROC) curve and immunohistochemistry were used to verify the diagnostic value and expression of hub genes in different invasive tumors. In summary, we investigated the biological behavior of stromal cells in the TME of MIBC to promote tumor progression obtained hub genes associated with progression and poor prognosis and identified the main stromal cells types in the TME. Abstract : Through our analysis, we found that stromal cells are closely related to the clinical prognosis of patients. Stromal cells are mainly involved in cell migration, leukocyte activation, and PI3K/AKT, MAPK, and Rap1 signaling pathways in tumor progression. In addition, we identified the hub genes of stromal cells promoting tumor progression based on bioinformatics analysis, and further identified chondrocytes and fibroblasts as the main types of 13 stromal cells.